Teaching business ethics - Gandz, Jeffrey (Journal of business ethics, 1988)
Business ethics should be taught in business schools as an integrated part of core curricula in MBA programs with a dual focus on both analytical frameworks and their applications to the business disciplines. To overcome the reluctance of many faculty to handle ethical issues, a critical mass of faculty must develop suitable materials, educate their peers in its use, and take the lead by introducing it in their own courses and on senior management programs.